Gluvi barut - Čengić, Bahrudin Bato (Yugoslavia : Forum Sarajevo ; Sutjeska Film Sarajevo ; RTV Sarajevo ; Jadran Film Zagreb, 1990)
Set in a Serbian village in the Bosnian mountains at the beginning of WWII, this atypical Yugoslav partisan film blurs the sides in the conflict. Most of Yugoslavia is already occupied, but resistance continues in this isolated mountain village where continuous clashes take place between Chetniks, local Nazi sympathizers and antifascist partisans. Partisan forces led by the communist party try to take over all anti-German attacks and the man chosen for the mission is Španac – an indoctrinated communist fanatic who wishes to “change the world” and does not care about the consequences or victims of his actions. His opponent is Radekić, former royalist officer still hesitant as to whether he should join the Chetniks or the partisans. A true expert in manipulating situations, Radekić is also an influential local who tries to rescue his people even at the price of his ideas. Soon the inhabitants, most of whom only wish to preserve their lifestyle, find themselves caught in the clash between two strong ideologies. Faced with the rebellion caused with Španac’s uncompromising attitude and methods, the party expels him and Radekić takes his place. Obedient to the party’s verdict, Španac leaves the village, but is killed by his former victim on his way out.
Keywords: Fiction films